An Atem Microstuctural Study of Kutnahorite - Khan, M. Riaz (Journal of Himalayan Earth Sciences, 1987)
The mineral kutnahorite, from Kutna Hora, Bohemia, is selected for investigations by means of analytical transmission electron microscopy. Major microstructural features observed are revealed as fringed ribbon-like defects and fine modulations in diffraction contrast images. The microstructures observed are clearly impurity related as determined by energy dispersive X-ray microanalysis. The ribbon-like defects are thin layers of second phase. They are coherent with the host phase. Diffraction patterns obtained from the modulated regions clearly show the elongation of the diffraction spots and in addition the “c" type spots are also observed on strongly exposed films. Such spots (“c" type) were previously observed in electron diffraction patterns from non-stoichiometric dolomites.